PUTRACOM: a concurrent component model with exogenous connectors - Nejati, Faranak; Abd Ghani, Abdul Azim; Ng, Keng Yap; Jaafar, Azmi (Institute of Electrical and Electronics Engineers (IEEE), 2018)
In component-based development (CBD), composing components and controlling the interactions among them is not a trivial task. The composition and interaction styles in the current state-of-the-art component-based models mostly are port-to-port connection or method-call based. However, both styles confer complex patterns, since the number of interactions may increase dramatically due to the number of method calls, ports, and connectors. To avoid such complexity, a simple and coherent component model with adequate policies for control is required. In this study, we provide a formal specification for components, composition and interactions issuing in discrete-events and non-blocking component-based systems. Our concurrent component model called PUTRACOM is equipped with Exogenous Connectors as third-party objects for coordination and Observable/Observable Unit (OOU) as a part of components for invocation. These are used to achieve a truly separation between computation and control in order to reduce the complexity that arises in port-to-port connection and method-call based interaction styles. To formally specify our model, we have adopted Communication Sequential Processes (CSP) and Reactive Transition Systems (RTS). The applicability of our model is evaluated using CoCoME case study. We demonstrate how PUTRACOM provides a mechanism to construct independent components and control the interactions between them by well-founded connectors.